2021
DOI: 10.1523/eneuro.0212-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

TRPM4 Contributes to Subthreshold Membrane Potential Oscillations in Multiple Mouse Pacemaker Neurons

Abstract: Select neuronal populations display steady rhythmic neuronal firing that provides tonic excitation to drive downstream networks and behaviors. In noradrenergic neurons of the locus coeruleus (LC), circadian neurons of the suprachiasmatic nucleus (SCN), and CO2/H+-activated neurons of the brainstem retrotrapezoid nucleus (RTN), large subthreshold membrane potential oscillations contribute to the pacemaker-like action potential discharge. The oscillations and firing in LC and SCN involve contributions from leak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Several studies suggested the role of TRPM4 in neuronal function on different brain regions including the hippocampus[21][31][32] the prefrontal cortex[33] and the pre-Bötzinger[34] complex however, most of these publications used pharmacological tools with questionable selectivity[25] to investigate TRPM4 function. Recently, two studies proved the expression of Trpm4 in brainstem pacemaker neurons using the ultrasensitive RNAscope in situ hybridization technique[35][36]. Our findings extend these results.…”
Section: Discussionsupporting
confidence: 86%
“…Several studies suggested the role of TRPM4 in neuronal function on different brain regions including the hippocampus[21][31][32] the prefrontal cortex[33] and the pre-Bötzinger[34] complex however, most of these publications used pharmacological tools with questionable selectivity[25] to investigate TRPM4 function. Recently, two studies proved the expression of Trpm4 in brainstem pacemaker neurons using the ultrasensitive RNAscope in situ hybridization technique[35][36]. Our findings extend these results.…”
Section: Discussionsupporting
confidence: 86%
“…4b ). Further, a TRPM4 blocker, CBA, that has no significant activity against TRPM8 49 , 50 , did not affect the lightening induced by cooling at any of the tested concentrations (Fig. 4c ).…”
Section: Resultsmentioning
confidence: 90%
“…Several studies suggested the role of TRPM4 in neuronal function on different brain regions including the hippocampus [ 19 , 30 , 31 ], the prefrontal cortex [ 32 ], and the pre-Bötzinger [ 33 ] complex; however, most of these publications used pharmacological tools with questionable selectivity [ 24 ] to investigate TRPM4 function. Recently, two studies proved the expression of Trpm4 in brainstem pacemaker neurons using the ultrasensitive RNAscope in situ hybridization technique [ 34 , 35 ]. Our findings extend these results.…”
Section: Discussionmentioning
confidence: 99%